Development of Science Learning Models Based on Islamic Values for Strengthening Scientific Literacy and Religious Character of Elementary School Students - Saukani Nur Akbar Saputra; Khamam Khosiin; Benny Prasetya (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This study aims to develop an Islamic values-based science learning model to strengthen scientific literacy and religious character among elementary school students. The study employed a Research and Development (R&D) approach using the ADDIE development model, consisting of analysis, design, development, implementation, and evaluation stages. The research participants included science education experts, Islamic education experts, elementary school teachers, and students selected purposively according to the research objectives. Data were collected through expert validation sheets, observations, interviews, questionnaires, scientific literacy tests, and religious character assessment instruments. The data were analyzed using descriptive statistics, effectiveness testing, and qualitative thematic analysis. The findings revealed that the developed model was valid, practical, and effective for elementary science learning. The model integrates scientific inquiry activities with Islamic values through five learning stages: orientation toward natural phenomena, scientific exploration, evidence-based explanation, Islamic value reflection, and application of scientific concepts in daily life. The implementation of the model improved students’ scientific literacy, particularly in explaining phenomena, interpreting evidence, analyzing information, and making scientific conclusions. In addition, the model strengthened students’ religious character through honesty, responsibility, environmental awareness, gratitude, and collaborative attitudes. This study contributes a comprehensive instructional framework that integrates scientific competence and Islamic character development within elementary science education.